A Well-To-Wheel Analysis of Greenhouse Gas Emissions for Electric Vehicle (EV) and Internal Combustion Engine Vehicle (ICEV) - NUR ANIS BINTI SAFIEI,; NORIRDA BINTI MOHAMED, (Progress in Engineering Application and Technology, 2025)
The automobile sector in Malaysia is expanding, and in 2023, it is expected to reach a record high of over 700,000 units for the second year in a row. Transportation is one of the contributors to several environmental burdens such as Greenhouse gas (GHG) emissions and resource depletion. This study aims to compare the GHG emissions Carbon Dioxide (CO2) between Internal Combustion Engine Vehicles (ICEVs) and Electric Vehicles (EVs) using a Life Cycle Assessment (LCA). Additionally, this study will also provide the environmental impact of using the existing mixed sources of electrical energy for an EV. The analysis follows a Well-to-Wheel approach, which captures the life cycle of the chosen vehicles during the production of energy (petrol and electricity) and their use phase. Volvo XC40 ICE and Volvo XC40 Recharge from C-segment car models are chosen to conduct the analysis. The analysis shows that EV model produce lower GHG emissions (16974 g CO2 eq./km) when compared to ICE model (38339 g CO2q eq/km) with 55.72% of CO2 reduction. The study also provides the comparison of GHG emissions between the calculated data and data obtained from Gabi Software to see if the calculated data is valid. This comparison emphasizes the potential for EVs to help decrease transportation-related emissions, even in areas like Malaysia that rely on a relatively high-carbon electricity mix. This study will enlighten the society on the importance of the adoption of low-emission vehicles